Narciclasine inhibits phospholipase A2 and regulates phospholipid metabolism to ameliorate psoriasis-like dermatitis - Kong, Yi; Jiang, Jian; Huang, Yuqiong; Liu, Xin; Jin, Zilin; Li, Li; Wei, Fen; Liu, Xinxin; Yin, Jie; Zhang, Yonghui; Tong, Qingyi; Chen, Hongxiang (Frontiers in Immunology, 2023)
Psoriasis is a common inflammatory skin disease recognized by the World Health Organization as "an incurable chronic, noninfectious, painful, disfiguring and disabling disease." The fact that metabolic syndrome (MetS) is the most common and important comorbidities of psoriasis suggests an important role of lipid metabolism in the pathogenesis of psoriasis. Narciclasine (Ncs) is an alkaloid isolated from the Amaryllidaceae plants. Its biological activities include antitumor, antibacterial, anti-inflammatory, anti-angiogenic and promoting energy expenditure to improve diet-induced obesity. Here, we report that Ncs may be a potential candidate for psoriasis, acting at both the organismal and cellular levels. Ncs can inhibit keratinocyte proliferation and reduce the recruitment of immune cells in the skin by inhibiting psoriasis-associated inflammatory mediators. In addition, it showed a direct repression effect on Th17 cell polarization. Transcriptomic and lipidomic data further revealed that Ncs extensively regulated lipid metabolism-related genes, especially the Phospholipase A2 (PLA2) family, and increased anti-inflammatory lipid molecules. Combined with single-cell data analysis, we confirmed that keratinocytes are the main cells in which Ncs functions. Taken together, our findings indicate that Ncs alleviates psoriasiform skin inflammation in mice, which is associated with inhibition of PLA2 in keratinocytes and improved phospholipid metabolism. Ncs has the potential for further development as a novel anti-psoriasis drug.